2009
DOI: 10.1021/la902770p
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and Reduction Processes in the Synthesis of Dendrimer-Encapsulated Pt Nanoparticles

Abstract: We synthesized Pt nanoparticles encapsulated in poly(amidoamine) (PAMAM) dendrimers by Pt(2+) coordination and subsequent reduction by NaBH(4). To optimize the experimental conditions for the Pt nanoparticle synthesis, we systematically examined the effects of pH, temperature, coordination time, and surface functional groups of the dendrimers on coordination and NaBH(4) reduction by UV-vis spectroscopy and transmission electron microscopy (TEM) measurements. We used generation-4 dendrimers (hydroxyl-terminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 76 publications
4
32
0
Order By: Relevance
“…After reduction, the obtained Pt NPs are confined in the cavity of dendrimer and the growth of Pt NPs is restricted by dendrimer. The Pt 40 obtained in G4-PAMAMA dendrimer in the previous work had a size of 1.4 ± 0.3 nm [34], which is accordance with our result ( Table 1). The diameter of the globular G4-PAMAM is 4.5 nm.…”
Section: Sample Characterizationsupporting
confidence: 92%
“…After reduction, the obtained Pt NPs are confined in the cavity of dendrimer and the growth of Pt NPs is restricted by dendrimer. The Pt 40 obtained in G4-PAMAMA dendrimer in the previous work had a size of 1.4 ± 0.3 nm [34], which is accordance with our result ( Table 1). The diameter of the globular G4-PAMAM is 4.5 nm.…”
Section: Sample Characterizationsupporting
confidence: 92%
“…Pb atoms were successively added to the lowest energy site on the Au particle, and the particle was relaxed before the addition of the next atom. The adsorption energy of the n th Pb atom, E ad (n), was calculated using eqn (2).…”
Section: Pb Upd Dft Calculationsmentioning
confidence: 99%
“…[1][2][3][4] Variations of this homogeneous synthetic method have yielded bimetallic DENs having different configurations, including random alloy and core@shell structures. 5 We have also developed electrochemical methods for synthesizing core@shell DENs.…”
Section: Introductionmentioning
confidence: 99%
“…The LMCT is interpreted as a transfer of electrons from the HOMO of the tertiary amine to the metal center LUMO. Many researchers (Knecht et al 2008a, b;Yamamoto et al 2010Yamamoto et al , 2011Zhao and Crooks 1999;Zhao et al 1998) have identified this phenomenon as a method to demonstrate and track the complexation process. For the metal ions selected in this work, the LMCT bands largely appear in the 230-400 nm range of the UV-Vis spectra.…”
Section: Batch Metal Ion Remediation Studies By Dendrimers In Aqueousmentioning
confidence: 99%
“…The multifunctional nature of dendrimer macromolecules (Astruc et al 2010;Lee et al 2005;Myers et al 2011;Tomalia et al 1990) offers potential advancements for a number of technological applications including drug delivery (Esfand and Tomalia 2001;Kitchens and Ghandehari 2009), nanoparticle synthesis (Bronstein and Shifrina 2011;Kuhn et al 2008;Witham et al 2010;Yamamoto et al 2010;Ye et al 2007), and environmental remediation (Diallo et al 1999(Diallo et al , 2004(Diallo et al , 2005Xu and Zhao 2005). Dendrimers are specifically enticing for environmental purposes because of the high density of internal functional groups and the ability to alter the chemistry of the external functional groups.…”
Section: Introductionmentioning
confidence: 99%